2015
DOI: 10.1038/icb.2015.42
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte:T‐cell interaction regulates human T‐cell activation through a CD28/CD46 crosstalk

Abstract: T cell activation requires engagement of the T cell receptor and of at least one costimulatory molecule. The key role of CD28 in inducing T cell activation has been reported several decades ago and the molecular mechanisms involved well described. The complement regulator CD46 also acts as a costimulatory molecule for T cells but, in contrast to CD28, has the ability to drive T cell differentiation from producing some IFNγ to secreting some potent anti-inflammatory IL-10, acquiring a so-called Type I regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…43 In a study, it was stated that un-stimulated monocytes have the ability to modulate T cell activation in the culture wells, because monocytes can undergo slight differentiation after plating into culture wells. 44 A current study suggested that resting monocytes of non-atopic asthmatic patients showed low expression of CD80 and high expression of CD86 when stimulated with LPS in the culture. 45 In this study, we investigated the effect of DFSCs on the activation of costimulatory molecules on monocytes in PBMC.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…43 In a study, it was stated that un-stimulated monocytes have the ability to modulate T cell activation in the culture wells, because monocytes can undergo slight differentiation after plating into culture wells. 44 A current study suggested that resting monocytes of non-atopic asthmatic patients showed low expression of CD80 and high expression of CD86 when stimulated with LPS in the culture. 45 In this study, we investigated the effect of DFSCs on the activation of costimulatory molecules on monocytes in PBMC.…”
Section: Discussionmentioning
confidence: 73%
“…The initiation of signalling mechanism begins with the presentation of antigens by MHC‐class II and activation of costimulatory molecules (CD80, CD83 and CD86), which CD86 induced with allergen‐specific responses . In a study, it was stated that un‐stimulated monocytes have the ability to modulate T cell activation in the culture wells, because monocytes can undergo slight differentiation after plating into culture wells . A current study suggested that resting monocytes of non‐atopic asthmatic patients showed low expression of CD80 and high expression of CD86 when stimulated with LPS in the culture .…”
Section: Discussionmentioning
confidence: 86%
“…17,20 The level of IL-10 production from macrophages/ monocytes could have been influenced by the lower absolute counts of T cells in young mice 41 but follow-up studies will be needed to confirm this. Moreover, from prior studies, 42,43 there are clear links between interactions of CD4 T cells and monocytes that affect each other's activities. At present, we do not know if differences in absolute T-cell counts, loss of IL-10 co-producing T cells in the lymph nodes that feed the lungs, a failure of young dendritic cells to adequately prime for co-producing cells, or whether other local lung factors that influence IL-10 co-production are not present in young mice.…”
Section: Discussionmentioning
confidence: 97%
“…Studying the coculture systems of T cells and monocytes is important to identify different mechanisms in the progression and therapeutic effects of several diseases such as cancer, inflammatory diseases, arthritis, and neurodegenerative diseases (49,50). To demonstrate the simultaneous measurement of cell proliferation in a mixed coculture, we applied the dye dilution assay to mixed populations: cocultures comprising (i) suspension type cells Jurkat and THP-1, and (ii) adherent and suspension type cells, U2OS and THP-1.…”
Section: Simultaneous Measurement Of Cell Proliferation Of Two Differmentioning
confidence: 99%
“…Playing a role in immune defense, T cells and monocytes are rapidly recruited to eliminate infected or transformed cells at the sites of infection or inflammation, and cocultures are often used to study various factors involved in their interaction. Studying the coculture systems of T cells and monocytes is important to identify different mechanisms in the progression and therapeutic effects of several diseases such as cancer, inflammatory diseases, arthritis, and neurodegenerative diseases (49,50). Also, the crosstalk between immune cells and cancer cells is important in cancer progression and metastasis in many cancers including osteocarcinoma (51) and adenocarcinoma (52).…”
Section: Simultaneous Measurement Of Cell Proliferation Of Two Differmentioning
confidence: 99%